CONSERVATION OF TERNATE LANGUAGE THROUGH POP ARTS IN MULTILINGUAL COMMUNITIES ON TERNATE ISLAND - Ajam, M. Ridha; Rauf, Ramis; Maricar, Farida; Subuh, Rahma Do; Majid, Arlinah (International Journal of Transdisciplinary Knowledge, 2023)
Language conservation is one solution to maintaining a language’s vitality, especially in a multi-ethnic society. This study aims to describe the condition of the regional language of Ternate, which continues to be eroded due to negative language attitudes due to the accommodation of native speakers who, in their daily interactions, constantly interact with other ethnic groups. This interaction is unavoidable, considering that the island of Ternate is a transit center for various modes of transportation, both by sea and by air. Aside from being a transit center, the island, with an area of ± 47 km2, is also the center of economic turnover for the North Maluku region. Language conservation through pop arts can be a solution to maintain the vitality of the Ternate language from the threat of extinction. This paper uses the Howard Giles approach, communication accommodation. This communication accommodation approach is related to interpersonal adjustment in a communication interaction. The analysis results in the form of a classification of types of art can be followed up by exploring various types of folk arts and the values contained in these arts.